Relative age effects in European soccer: their association with contextual factors, impact on youth national teams' performance, and presence at the senior level - Morganti, Gabriele; Kelly, Adam L.; Lascu, Alexandra; Brustio, Paolo R.; Padua, Elvira; Filetti, Cristoforo; Porta, Marco; Briotti, Gianluca; Ruscello, Bruno (Frontiers in Sports and Active Living, 2025)
IntroductionSoccer systems promote early identification and specialisation practices to satisfy short- and long-term goals—both from sporting performance and financial gains perspectives. In this context, players are (de)selected based on observed performance level and on their ability to conform to given organisational demands, leading to the proliferation of selection biases, such as relative age effects (RAEs), which research has shown to influence both developmental experiences and senior career achievements. Accordingly, this study aims to: (a) investigate the magnitude of RAEs among youth national teams competing in the UEFA U17 European Soccer Championship, and their associations with teams' final ranking, (b) examine whether RAEs magnitude could be linked to cultural and contextual factors, and (c) further explore RAEs at senior level.MethodsBirth quarter (BQ) distribution of youth national teams (n = 80) that competed in one of the five editions (2018, 2019, 2022, 2023, and 2024) of the UEFA U17 European Soccer Championship was recorded. Teams were classified based on their country of origin, RAEs magnitudes, final ranking in the tournament, FIFA points, and national population. Furthermore, the BQ distribution of senior national teams (n = 24) that competed at the 2024 UEFA Senior European Soccer Championship was recorded.ResultsChi-square statistics revealed BQ1s were overrepresented at the U17 level (p < 0.001) and showed teams exhibiting low RAEs magnitudes recorded the highest likelihood (odds ratio: 5.67) of finishing the tournament in the bottom four positions. Correlation analyses recorded small to moderate positive correlations between RAEs magnitude and national population (.25) and FIFA points (.33). Further chi-square statistics revealed BQ1s continued to be overrepresented at the senior level, albeit with a weaker effect (p < 0.001). However, when the senior BQ distribution was compared to the expected distribution taken from the U17 population, this recorded more BQ4s and fewer BQ1s than expected (p < 0.001).DiscussionThe findings presented the focus on youth success, the increased talent pool size, and the competition for selection interact to reiterate RAEs' prevalence in European soccer. Moreover, they highlighted initial RAEs define players' journey within the soccer system, whereby relatively older players remain overrepresented at the senior level, albeit to a weaker and lesser extent.